Unlocking the secrets of the Fed : how monetary policy affects the economy and your wealth-creation potential - Jones, David M. (David Milton) (Hoboken, NJ : Wiley, 2002)
This book gets inside the world of monetary and fiscal policymaking and explains how understanding and anticipating the actions of the Federal Reserve is critical to your investment success.
Includes bibliographical reference (p. 229-234) and index
rpm 07/05/13
Loans
Keywords: Monetary policy -- United States; Board of Governors of the Federal Reserve System (U.S.)